Growth and Yield of Corn Plants Against Vermicompost Dosage in Degraded Ultisols - Zikri, Ahmad; Utami, Kartika; Anggraini, Septiana; Suprijono, Eko; Widodo (BPFP Universitas Bengkulu, 2023)
Ultisols has prominent weaknesses and problems such as high acidity levels, low water absorption capacity, and low nutrient content such as N, P, K, Ca, and Mg, so it has the potential to inhibit plant growth. One way to overcome Ultisols soil problems is to use vermicompost fertilizer. Corn is one of the plants that is suitable for cultivation using vermicompost fertilizer. The research aims to obtain the best dose of vermicompost for corn growth and yield in degraded Ultisol soil. The research was conducted in Sri Kuncoro Village, Pondok Kelapa District, Central Bengkulu Regency, Bengkulu Province. The design used a single-factor Complete Randomized Block Design (RCBD) consisting of 5 treatment levels and five replications to obtain 25 experimental plots of 0, 7.5, 15, 22.5, and 30 tons ha-1. Data were analyzed using Analysis of Variance (ANOVA) at a 5% level and continued with the Least Significant Difference (LSD) test at a 5% level. The research results showed that the dose of vermicompost significantly affected the variables of plant height, number of leaves, number of leaves, and plant dry weight. The best vermicompost treatment dose was 22.5 tons ha-1 with plant height 254.85 cm, number of leaves 13.26, stem diameter 24.90 mm, leaf area 811.49 cm2 , cob length with husk 24, 93 cm, cob length without husk 17.26 cm, cob weight with husk 218.19 g, cob weight without husk 194.26 g, dry seed weight of plant samples 153.33 g and Dry seed weight per ha 9.1 tons.